Comparison of Clinical Outcomes between Phacoemulsification and Laser Peripheral Iridotomy in the Spectrum of Primary Angle Closure Diseases of the Eye - Manoa Panjaitan; Widya Artini (Majalah Oftalmologi Indonesia, 2016)
Background: To compare clinical outcome between phacoemulsification and laser peripheral iridotomyin the spectrum of primary angle closure eyes.Methods: A literature review of databases were retrieved online through Pub-med, Clinical Key, andScience Direct, using keywords of ‘primary angle closure’, ‘primary angle closure glaucoma’, and‘acute primary angle closure’. In addition, all literatures involving the use of laser peripheral iridotomy(LPI) or phacoemulsification as a treatment in PAC diseases were included. Publications and journalsbefore the year 2000 were excluded.Results: There were 18 articles that fulfilled our inclusion criteria. All of the studies showed a decreasein IOP following cataract extraction or LPI, compared to baseline. This study also showed that thephacoemulsification group gave a significantly larger angle width increment when compare to LPI.When directly compared between phaco to LPI, the number of topical glaucoma medication was moredecreased in the phaco group, meanwhile the need for additional glaucoma surgery was higher in theLPI group.Conclusion: Phacoemulsification with posterior chamber lens implantation is more effective procedurethan LPI in lowering IOP and preventing IOP rise in long term follow up in PAC diseases. That surgerywill reduce the number of additional glaucoma medication and further glaucoma filtering surgery.Despite of superiority in phacoemulsification treatment, LPI is still the mainstay of initial treatment,especially in PAC eye diseases without cataract.Keywords: spectrum of primary angle closure eye disease, phacoemulsification, laser peripheral iridotomy, angle width